Rights of Protection, Maintenance and Welfare of Parents and Senior Citizens in India: Exploring the Fundamental Rights and Welfare of Parents and Senior Citizens in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human Rights are the basic rights which fundamentally and inherently belong to each individual. In other word these are the freedoms established by custom or international agreement that impose standards of conduct on all nations. These rights are distinct from civil liberties, which are freedoms established by the law of a particular state and applied by that state in its own jurisdiction. Thus, these are the Fundamental rights which human being possesses by the fact of being human, and which are neither created nor can be abrogated by any government.